Integrasi Teknik Gambar Self-Directed Learning dan Tutor Sebaya dalam Meningkatkan Kemampuan Menggambar Siswa - Rachmawati, Surya Anita; Supardji, Supardji (Jurnal Pendidikan Madrasah, 2024)
Drawing ability is one of the important competencies in the field of engineering and art education, which requires conceptual understanding, creativity, and technical skills. This study aims to analyse the effectiveness of the integration of Self-Directed Learning (SDL) techniques and peer tutor methods in improving students' drawing skills. SDL's approach encourages students to independently plan, execute, and evaluate their learning process, while the peer tutor method optimizes social interaction to strengthen understanding and skills. The results of the study show that the integration of SDL techniques and peer tutors provides a holistic approach to drawing learning, which not only improves technical abilities but also builds students' independence and social skills. The recommendations of this study include the development of SDL-based interactive modules and peer tutor training to support wider implementation.